Association of intraoperative opioid administration with postoperative pain and opioid use - Amjid Ali; Jawad Hameed; Ayesha Mairaj; Abid Haleem Khattak; Hadiqa tul Batool; Syed Faraz Bukhari (Medical Journal of South Punjab, 2024)
Objective:The primary goal of this study is to examine the impact of incentive spirometry andpeak expiratory flow meter on risks of cardiopulmonary sequelae following valve surgery.Methods:The study was conducted on36 patients operated under general anaesthesia at Lady reading hospital Peshawar. We analyzed whether the total intraoperative opioid dose predicts 30-day hospital readmission after controlling for various patient-, anaesthetist-, and case-specific factors.Results: Ambulatory surgical patients who received high intraoperative opioid doses had a substantially increased risk of readmission within 30 days after discharge. The largest adjusted risk of readmission was seen in patients receiving high doses of opioids (OR: 1.75; P